Brazil's Nuclear Policy. From Technological Dependence to Civil Nuclear Power - Daniel Flemes (German Institute of Global and Area Studies (GIGA), 2006)
Since March 2006 Brazil has been the ninth country to control the full nuclear fuel cycle. While the U.S. government bashes the uranium enrichment activities in Iran, it has come to an arrangement with the uranium enrichment in its backyard after transitional diplomatic tensions. As signer of the Non-Proliferation Treaty Brazil has the right to enrich uranium for peaceful use. This article focuses on the political motives and objectives connected with the domination of this key technology. Brasilia has been striving for regional leadership and participation in international decision making processes. In historical perspective the Brazilian enrichment procedure marks the liberation from the technological U.S. dependence. Brazil seems to be on the way to establish itself as a civil nuclear power in international relations. – – Brasilien beherrscht seit Anfang Mai 2006 als neuntes Land der Welt den vollständigen Brennstoffkreislauf. Während die US-Regierung die Urananreicherungsaktivitäten im Iran scharf verurteilt, hat sie sich nach vorübergehenden diplomatischen Spannungen mit mit der Urananreicherung in ihrem geostrategischen 'Hinterhof' arrangiert. Als Signatarstaat des Atomwaffensperrvertrags hat Brasilien das Recht, zur zivilen Nutzung Uran anzureichern. Dennoch stellt sich die Frage nach den politischen Zielen und Motiven, die mit der Beherrschung dieser Schlüsseltechnologie verbunden sind. Neben energiepolitischen Motiven bemüht sich Brasilia seit langem darum, sein Profil als regionale Führungsmacht zu schärfen. Vor dem Hintergrund der jüngsten Entwicklungen der globalen Nuklearpolitik ist Brasilien auf dem Weg, sich als zivile Nuklearmacht zu etablieren.
Keywords: 300; Brazil; nuclear policy; uranium enrichment; Non-Proliferation Treaty; US foreign policy; Kernenergie; Kernenergiepolitik; Brasilien